Amyloid-beta induced paralysis is reduced by cholecalciferol through inhibition of the steroid-signaling pathway in an Alzheimer model of Caenorhabditis elegans. (1st February 2021) - Leiteritz, Anne; Schmiedl, Tommy; Baumanns, Stefan; Wenzel, Uwe
ABSTRACT: Objectives: Alzheimer's disease (AD) is a neurodegenerative disorder resulting from the accumulation of toxic β-amyloid (Aβ) aggregates in the human brain. Epidemiological studies have shown that elevated cholesterol plasma levels are associated with the development of AD and we have previously shown that cholesterol restriction reduces the Aβ-induced paralysis in an Alzheimer model of the nematode Caenorhabditis elegans. In the present study we investigated the effects of the cholesterol homolog cholecalciferol, i.e. vitamin D, on Aβ-induced paralysis in C. elegans and its interference with the steroid-signaling pathway. Methods: Aβ-induced paralysis was assessed in the C. elegans strain CL2006, expressing human Aβ1-42 under control of a muscle-specific promoter. Knockdown of members of the steroid-signaling pathway was achieved by RNA interference (RNAi). Nuclear translocation of foxo transcription factor DAF-16 was visualized using the strain TJ356, carrying a daf-16 :: gfp transgene. Results: Cholecalciferol at a concentration of 1 µM reduced the Aβ-induced paralysis in CL2006 significantly, which was reverted by increasing the cholesterol concentration in the medium. Knockdown of nhr-8, daf-36, daf-9 or daf-12, all reduced Aβ-induced paralysis to the same extent as cholecalciferol with no additional or synergistic effects under co-application. Functional DAF-16 proved to be crucial for the effects of cholecalciferol and DAF-16 nuclear translocation was increased by cholecalciferol and also RNAi versus nhr-8, daf-36, daf-9 or daf-12 with no additive or synergistic effects. Conclusions: Our results suggest, that cholecalciferol inhibits Aβ-induced paralysis in C. elegans through inhibition of steroid-signaling and the concomitant nuclear translocation of DAF-16.